AESTHETIC ANALYSIS OF CARVING THE ATMOSPHERE OF RURAL MARKETS IN THE MIDST OF THE DEGRADATION OF YOUTH INTEREST IN SENENAN VILLAGE - Amelia Lysanties; Wasis Wijayanto (Universitas Negeri Semarang, 2025)
Jepara is known as the